Recent Evolution of the Personal Privacy Legal Protection in People’s Republic of China - Moriconi, Corrado (NAVEIÑ REET: Nordic Journal of Law and Social Research, 2020)
This article explores the current legal protection of personal information in the People’s Republic of China. The P.R.C. has rapidly developed legislatively and academically with comprehensive Chinese data protection regulation closely integrated with all new developments. Currently, the legal framework appeared to be fragmented in that it is composed of widely varying laws and regulations. This article will offer a description of the evolution of the modern concept of privacy within the context of Chinese political and societal norms. The relevant regulations and their development will be addressed relative to significant cases. Conclusions and perspectives on possible future improvements are described in a general summary.